Analisa BOK (Biaya Operasi Kendaraan) Shuttle Service Rute Bandung â€“ Jakarta Selatan - Akbardin, Juang; Putra, Andri Eka (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
The opening of the toll road Cipularang provide opportunities for business people open a travel service (shuttle service) â€œpoint to pointâ€ are scattered in several points in Bandung. Another phenomenon occurs on the field gap between the performance of the travel srvices to the satisfaction of passengers. This, prompted the authors to conduct a study of the level of analytic of vehicle operating cost for services of travel. Due to limited funds, manpower, and time, the scope of this final study is limited to the South Jakarta â€“ Bandung route. The purpose of this study was to measure and compare the performance of the travel (shuttle service) Bandung- South Jakarta route to the satisfaction of passengers. In this study using quantitative methods with descriptive analysis techniques. The data used were obtained from the results of a questionnaire survey / questionnaire and interview. The sampling technique is Probability Sampling is done using simple random sampling method with a sample of 390 respondents taken as users travel (shuttle service) Bandung- South Jakarta route. Data analysis using the method of Importance Performance Analysis. Based on the analysis, a gap in variable costs, travel time, and travel itineraries. Variable costs and passenger safety is still not good and a top priority for improvement.